2020
DOI: 10.1186/s12888-020-02925-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting therapeutic response to oral ketamine for chronic suicidal ideation: a Bayesian network for clinical decision support

Abstract: Background The glutamatergic modulator ketamine has been shown to result in rapid reductions in both suicidal ideation (SI) and depressive symptoms in clinical trials. There is a practical need for identification of pre-treatment predictors of ketamine response. Previous studies indicate links between treatment response and body mass index (BMI), depression symptoms and previous suicide attempts. Our aim was to explore the use of clinical and demographic factors to predict response to serial do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The primary clinical outcome measure was reduction in suicidality with ketamine treatment, and this was determined by Beck Scale for Suicide Ideation (BSS) ( Can et al, 2021 ). Secondary clinical measures used in this study included the Depression Anxiety Stress Scale 21 (DASS-21) ( Beaudequin et al, 2020 ; Dutton et al, 2022 ). In total, assessments at each major timepoint required approximately 8 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The primary clinical outcome measure was reduction in suicidality with ketamine treatment, and this was determined by Beck Scale for Suicide Ideation (BSS) ( Can et al, 2021 ). Secondary clinical measures used in this study included the Depression Anxiety Stress Scale 21 (DASS-21) ( Beaudequin et al, 2020 ; Dutton et al, 2022 ). In total, assessments at each major timepoint required approximately 8 hours.…”
Section: Methodsmentioning
confidence: 99%
“…62 Using Bayesian networks and data from a longitudinal open study in patients with chronic suicidal ideation, one group showed that younger age, female gender, normal body mass index, higher level of education, being single, being unemployed, previous suicide attempts, and suffering from a less severe level of depression all predicted a prolonged response to oral ketamine. 63 Finally, one study showed a good predictive capacity for the anti-suicidal response to ketamine by a combination of an early clinical response and early measures of kynurenic acid levels in serum. 64…”
Section: Predictive Clinical Markers Of Response To Ketaminementioning
confidence: 99%
“…The model has no strict requirements regarding data distribution; therefore, it can incorporate all the data to reveal the influences of various factors on mental health and the relationships between them. BNs have been widely used in many fields, including social and behavioral science (Aghaabbasi et al, 2020), clinical science (Beaudequin et al, 2020), occupational health (García-Herrero et al, 2017). However, no study to date has used a BN model to investigate the psychological impacts of the COVID-19 epidemic on populations.…”
Section: Introductionmentioning
confidence: 99%